The Many-Player Advertising Game - Fruchter, Gila E. (Management Science, 1999)
This study extends the time-variant closed-loop strategy of Fruchter and Kalish (1997) to the n-player advertising game. We demonstrate that solving an n-player game using 2 players results in overadvertising.